Inhibition of Nitride Precipitation in a Fe-Cr-Mn-Mo-N High-Nitrogen Austenitic Stainless Steel through Grain Boundary Character Distribution Optimization. Issue 1 (May 2021) - Shi, F; Hu, J; Wang, L F; Guan, X J; Liu, CM; Li, X W
Abstract: The precipitation behavior of the second phase in Fe-18Cr-17Mn-2Mo-0.85N high nitrogen and nickel-free austenitic stainless steel after grain boundary character distribution (GBCD) optimization was investigated. The results show that the fraction of low Σ coincidence site lattice (CSL) boundaries increases from 47.9% for the solid solution treated specimen to 82.25% for the specimen cold-rolled by 5% and then annealed at 1423 K for 72 h (r5%-a1423 K/72 h). Compared with the solution treated sample, nitride precipitation is obviously restrained and the fraction of precipitates is the least in r5%-a1423 K/72 h sample with the highest proportion of SBs. The appearance of a high proportion of CSL boundaries with low energy inhibits the nitrides precipitation through GBCD optimization.